2015
DOI: 10.1136/bmjopen-2014-006723
|View full text |Cite
|
Sign up to set email alerts
|

Daptomycin plus fosfomycin versus daptomycin monotherapy in treating MRSA: protocol of a multicentre, randomised, phase III trial

Abstract: IntroductionDespite the availability of new antibiotics such as daptomycin, methicillin-resistant Staphylococcus aureus (MRSA) bacteraemia continues to be associated with high clinical failure rates. Combination therapy has been proposed as an alternative to improve outcomes but there is a lack of clinical studies. The study aims to demonstrate that combination of daptomycin plus fosfomycin achieves higher clinical success rates in the treatment of MRSA bacteraemia than daptomycin alone.Methods and analysisA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 26 publications
1
18
0
2
Order By: Relevance
“…In addition, several of them were conducted years or even decades ago, and their findings may not apply to the resistance profiles of contemporary isolates or the complexity and severity of diseases and infections that patients face nowadays. Data from RCTs are still not available, but RCTs evaluating the comparative efficacy of fosfomycin and meropenem for bacteremic UTIs and fosfomycin in addition to daptomycin for MRSA bacteremia are under way (238,239). Similarly, fosfomycin is being evaluated in combination with other antibiotics for MDR or XDR infections (NCT01297894, NCT02142751, and NCT00871104).…”
Section: Non-urinary Tract Infectionsmentioning
confidence: 99%
“…In addition, several of them were conducted years or even decades ago, and their findings may not apply to the resistance profiles of contemporary isolates or the complexity and severity of diseases and infections that patients face nowadays. Data from RCTs are still not available, but RCTs evaluating the comparative efficacy of fosfomycin and meropenem for bacteremic UTIs and fosfomycin in addition to daptomycin for MRSA bacteremia are under way (238,239). Similarly, fosfomycin is being evaluated in combination with other antibiotics for MDR or XDR infections (NCT01297894, NCT02142751, and NCT00871104).…”
Section: Non-urinary Tract Infectionsmentioning
confidence: 99%
“…Fosfomycin doses of 3 g orally have been well established to treat UTIs, and bloodstream infections have been treated with fosfomycin at 50 mg/kg of body weight three to four times daily in combination with a ␤-lactam agent (4,8,9). Other studies have utilized fosfomycin doses of 2 g every 6 or 8 h (10,11). Developed in 1969, fosfomycin has drawn increasing attention for use in multidrug-resistant bacterial infections as combination therapy due to the increase in antimicrobial resistance and lack of novel antimicrobial development (6,12,13).…”
mentioning
confidence: 99%
“…Developed in 1969, fosfomycin has drawn increasing attention for use in multidrug-resistant bacterial infections as combination therapy due to the increase in antimicrobial resistance and lack of novel antimicrobial development (6,12,13). While most of the data on fosfomycin-based antimicrobial combinations come from small in vitro studies, clinical trials are ongoing in Europe to evaluate the combination of daptomycin and intravenous fosfomycin for treatment of MRSA bacteremia (11).…”
mentioning
confidence: 99%
“…It was shown that the addition of either oxacillin [52,53] or cloxacillin [54] might be beneficial in preventing daptomycin treatment failure. A multicenter open-label, randomized Phase III study is currently ongoing to test whether combination therapy of daptomycin plus fosfomycin may achieve higher clinical success rates in the treatment of MRSA bacteremia than daptomycin alone [55].…”
Section: Methicillin-resistantmentioning
confidence: 99%